NILAI MORAL DAN PATRIOTISME DALAM FILM DISNEY MOANA - Istiqamah, Istiqamah (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2020)
This study aims to describe moral values and patriotism in the Disney Moana film. This research uses descriptive qualitative method, research data source in the form of Disney Moana film. Data collection techniques in the form of literature study. Data analysis techniques in the form of techniques see. The results showed that the moral values contained in Disney Moana Film were (1) animal lover, (2) soft heartedness, (3) working together, (4) happy learning history, and (5) not giving up. Meanwhile, the value of patriotism contained in Disney Moana Film, namely (1) faithful friends, (2) never give up, (3) brave, (4) love the motherland, and (5) admit mistakes.Keywords: Value, morality, patriotism